MENINGKATKAN KEMAMPUAN GURU MATEMATIKA DALAM MENYUSUN RENCANA PELAKSANAAN PEMBELAJARAN MELALUI PENDAMPINGAN DI SMA BINAAN KABUPATEN LAMONGAN - Salamun Salamun (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2015)
lesson plans through Mentoring. The study design school action consists of three cycles, each cycle consisting of four activities, Including planning, implementation, observation, and reflection conducted in nine schools Patronage in Semester Academic Year 2014-2015. The subject of research is Professor of Mathematics at the School Patronage. Methods of analysis of data using descriptive statistical analysis techniques scoring the which is then converted into value. Indicators of success of this research is the average value of the ability of teachers to prepare lesson plans Reached 85. The analysis results Obtained in the first cycle of the average value is 70.7, the second cycle of the average value is 80.5 while the third cycle value the average is 86.9. From Reviews These results look the Increase in value from one cycle to the next cycle. The third cycle has exceeded the value Obtained indicator of the success of the study. Based on the results of the analysis can be concluded that the ability of Mathematics Teacher in write lesson plans can be improved through the assistance activities undertaken by the School Supervisor.